Phytochemical Profiling of Amazonian Herbal Medicinal Products: The Role of Traditional Processing Methods - Tresca, Marco Soffiato, Matteo Politi, Giorgia; Montes, Richer Garay; Mendive, Fernando (Journal of Medicinal Herbs and Ethnomedicine, 2019)
Research on traditional processing methods used to transform plants into medicines offers a valuable arena to investigate the correct formulation of herbal products. While scientific literature on traditional herbal medicines emphasizes the relevance of the taxonomical identification of the used species, the same rigor is not applied to recording the processing methods. In other words, attention is given to the ingredients, but not the recipes. This can not only jeopardize the quality of research on traditional herbal medicines, but also generate concerns once such medicines reach the global markets in compliance with modern manufacturing requirements, which are usually well far away from the traditional ones. In the present work, different traditional herbal medicines used in the region of San Martin, Peru, were analyzed by the means of UPLC-UV/DAD metabolite fingerprinting. Different extracts were prepared from same commercially available materials in order to test the effect of the recipes on the chemistry of the finished products. In particular, different plant parts and their status (fresh or dry), extraction solvents and decoction times were selected for metabolite comparisons between the extracts. In accord with literature data on others traditional pharmacopoeias, our results show how specific manufacturing steps can affect the chemistry of the finished products. Further efforts are necessary to evaluate the traditional herbal practices, whether understandable or not, with modern scientific approaches.